Basic Literacy in Social Studies Learning to Instill 21st Century Abilities of Semarang City Junior High School Students - Setiawati, Winda; Hardati, Puji; Sunarto, Sunarto (Universitas Negeri Semarang, 2025)
The emergence of social problems in students as a young generation due to the lack of 21st century skills, these problems include early marriage and feeling that education is enough. This study aims to analyze basic literacy in social studies learning to instill the 21st century abilities of junior high school students in Semarang City. This study uses a descriptive method with a qualitative approach. The locations in this study are SMP N 31 Semarang, SMP N 38 Semarang, SMP H. Isriati Semarang, and SMP Hasanudin 6 Semarang. The results of this study show that basic literacy in social studies learning to instill the 21st century abilities of junior high school students in Semarang City can be done with several comprehensive steps, including integrating basic literacy (literacy, financial literacy, digital literacy, and cultural and civic literacy) in social studies learning, the use of media and learning materials, as well as teacher training and competence improvement. Applying basic literacy in social studies learning can be used to instill the 21st century skills of junior high school students in Semarang City. The 21st century abilities include: character, citizenship , critical thinking, creativity, collaboration, and communication.